Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

Factors influencing the expression of human directed dog aggression. A qualitative study of professional opinion - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Water Exchange Characteristics of Tidally Influenced Hydrilla Invasion Sites in the Lower Connecticut River - Andrew W. Howell; Benjamin P. Sperry; Jens P. Beets; Michael W. Durham; Jonathan S. Glueckert; Amber E. Riner (Estuaries and Coasts, 2026)
The Lower Connecticut River (CR) is an ecologically and recreationally significant ecosystem within New England, but the river has become increasingly vulnerable to the intrusion of aquatic invasive species (AIS) like hydrilla ( Hydrilla verticillata ). The hydrilla population recently discovered in the Lower CR is genetically unlike former hydrilla clades present in the United States. The specific biological and management components of this unique clade-C hydrilla in comparison to its cohorts remains largely undetermined and the nature of management action to combat the submersed plant within the tidally influenced lotic system further complicates waterway resilience efforts due to high-water exchange. Because of the inherent environmental challenges attributed to lotic environs, the use of aquatic herbicides remains the primary management tool for selective and effective hydrilla control. However, knowledge of the site-specific water exchange processes at infested sites coupled with subspecies- and herbicide-specific concentration-exposure time (CET) requirements are essential for successful plant management. The primary goal of the present studies was to quantify bulk water exchange rates at five representative hydrilla infestation sites within the Lower CR using Rhodamine WT dye (RWT) to mimic prospective herbicide application operations. Dye monitoring indicated distinct variability among study site water exchange rates, with RWT half-lives ranging from 0.35 to 72.36 h following application. Future management efforts deploying herbicide should consider these methods and findings when selecting appropriate herbicide active ingredients and use rates to achieve hydrilla control. While the present water exchange findings offer initial guidance, comparable dye studies will be necessary as management programs target additional hydrilla invasion areas within the river.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Application of a population status model on several recreational lake trout (Salvelinus namaycush) fisheries in Manitoba, Canada - Giulio Navarroli; Bradley E. Howell; Andrew W. R. Klein; Eric J. Mullen; Olivier Morissette; Michael D. Rennie; Caleb T. Hasler (Environmental Biology of Fishes, 2025)

Characterization of adult hippocampal neurogenesis in adult and aged genetically diverse mice - Adele E. Finch; Avery D. McNamara; Kristen D. Onos; Kelly J. Keezer; Gareth R. Howell; Ashley E. Webb (GeroScience, 2025)
Adult hippocampal neurogenesis—the generation of new neurons in the adult brain—declines with age, contributing to cognitive deficits in aging. While the majority of mammalian studies on neurogenesis have utilized inbred mouse strains, these models do not fully capture the genetic diversity of humans, limiting the translational relevance of their findings. The Diversity Outbred (DO) mouse model, a genetically heterogeneous population, provides a promising alternative to traditional inbred strains. In this study, we investigated how genetic diversity influences hippocampal neurogenesis by comparing neurogenesis in adult and aged Diversity Outbred (DO) mice with the commonly used C57BL/6J inbred strain. While both strains exhibited a decline in neurogenesis with age, DO mice showed significantly lower levels of neurogenesis compared to C57BL/6J mice, even in young adults. Additionally, we observed that the wild-derived CAST/EiJ strain, one of the eight founder strains in the DO model, contributed to this reduction in neurogenesis. Our findings highlight the importance of genetic diversity in neurogenesis research and suggest that the DO model may better represent human genetic diversity associated with age-related decline in neurogenesis.

Exploring development of spatially stratified wind turbine collision risk prior distributions for eagles: An application of adaptive management - Paige E. Howell; Leslie New; Emily R. Bjerre; Hillary M. White (Journal of Environmental Management, 2025)

Development and Implementation of a 3-Week Whole-Food Plant-Based Vegan Diet Intervention for College Students - Sydeena E. Isaacs; Melinda Bogardus; Martie Thompson; Shenghui Wu; Marisa Howell (Journal of Nutrition Education and Behavior, 2025)

Alterations in murine macrophage reactivity and bactericidal efficacy following exposure to an environmentally relevant mixture of organochlorine pesticide compounds - George E. Howell; Darian Young; Keun Seok Seo; Maggie Tu (Food and Chemical Toxicology, 2025)

Risk factors for human-directed aggression by dogs: The human side of the problem. A two-part systematic review and narrative synthesis - Helen Howell; Ann Baslington-Davies; Daniel S. Mills; Todd E. Hogue (Applied Animal Behaviour Science, 2025)

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Corrigendum to “Plutonium and other radionuclides persist across marine-to-terrestrial ecotopes in the Montebello Islands sixty years after nuclear tests” [Sci. Total Environ. Volume 691, 15 November 2019, pages 572–583] - M.P. Johansen; D.P. Child; T. Cresswell; J.J. Harrison; M.A.C. Hotchkis; N.R. Howell; A. Johansen; S. Sdraulig; S. Thiruvoth; E. Young; S.D. Whiting (Science of The Total Environment, 2024)

Avian community responses to energy development and woody encroachment - John M. Yeiser; Paige E. Howell; Anna M. Matthews; Gregory T. Wann; Jim Giocomo; James A. Martin (Biological Conservation, 2024)

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Effects of an environmentally relevant mixture of organochlorine pesticide compounds on adipogenesis and adipocyte function in an immortalized human adipocyte model - George E. Howell; Darian Young (Toxicology in Vitro, 2024)

The Fastest Rotators: Near-Earth Asteroids Observed with the Arecibo Planetary Radar System - Luisa Fernanda Zambrano-Marin; Ellen S. Howell; Sean E. Marshall; Jon Giorgini; Flaviane C.F. Venditti (Icarus, 2024)

Practical methods for the control of tor-grass (Brachypodium pinnatum s.l.) and the restoration of calcareous grassland - Lucy E. Ridding; John W. Redhead; Emily V. Upcott; Lucy Hulmes; Sarah Hulmes; Nadine Mitschunas; Katherine Howell; Jenny Christelow; Alexander R. Wickenden; Mike Fussell; James Plunkett; Richard F. Pywell (Journal for Nature Conservation, 2024)

Trajectories and tipping points of piñon–juniper woodlands after fire and thinning - Michala L. Phillips; Cara Lauria; Tova Spector; John B. Bradford; Catherine Gehring; Brooke B. Osborne; Armin Howell; Edmund E. Grote; Renee J. Rondeau; Gillian M. Trimber; Benjamin Robinson; Sasha C. Reed (Global Change Biology, 2024)
Piñon–juniper (PJ) woodlands are a dominant community type across the Intermountain West, comprising over a million acres and experiencing critical effects from increasing wildfire. Large PJ mortality and regeneration failure after catastrophic wildfire have elevated concerns about the long‐term viability of PJ woodlands. Thinning is increasingly used to safeguard forests from fire and in an attempt to increase climate resilience. We have only a limited understanding of how fire and thinning will affect the structure and function of PJ ecosystems. Here, we examined vegetation structure, microclimate conditions, and PJ regeneration dynamics following ~20 years post‐fire and thinning treatments. We found that burned areas had undergone a state shift that did not show signs of returning to their previous state. This shift was characterized by (1) distinct plant community composition dominated by grasses; (2) a lack of PJ recruitment; (3) a decrease in the sizes of interspaces in between plants; (4) lower abundance of late successional biological soil crusts; (5) lower mean and minimum daily soil moisture values; (6) lower minimum daily vapor pressure deficit; and (7) higher photosynthetically active radiation. Thinning created distinct plant communities and served as an intermediate between intact and burned communities. More intensive thinning decreased PJ recruitment and late successional biocrust cover. Our results indicate that fire has the potential to create drier and more stressful microsite conditions, and that, in the absence of active management following fire, there may be shifts to persistent ecological states dominated by grasses. Additionally, more intensive thinning had a larger impact on community structure and recruitment than less intensive thinning, suggesting that careful consideration of goals could help avoid unintended consequences. While our results indicate the vulnerability of PJ ecosystems to fire, they also highlight management actions that could be adapted to create conditions that promote PJ re‐establishment.

A risk assessment for the remote ocean: the case of the South East Atlantic - Holly J. Niner; Siân E. Rees; Giulia La Bianca; Kirsty A. McQuaid; Kerry L. Howell (Frontiers in Marine Science, 2024)
Degradation of the natural world and associated ecosystem services is attributed to a historical failure to include its ‘value’ in decision-making. Uncertainty in the quantification of the relationship between natural capital ‘assets’ that give rise to critical societal benefits and people is one reason for the omission of these values from natural resource management. As this uncertainty increases in marine systems and further still with distance from the coast, the connection between society and natural capital assets is less likely to be included adequately in decision-making. Natural capital assets of Areas Beyond National Jurisdiction (ABNJ), including those of the deep sea, are distant but are known to generate many benefits for society, from the diffuse and broad-scale benefits of climate regulation to the provision of wild fish for food. While our understanding of the precise relationships (the status of asset stocks, ecosystem functions and processes) that control the availability of ecosystem services and the flows of benefits is limited, this does not preclude opening a discourse on how these natural capital assets could best be managed to continue to benefit society. Here we apply a natural capital approach to the South East Atlantic ABNJ, one of the least scientifically understood regions of the planet, and develop a framework for risk assessment. We do this by describing the benefit flows from the natural capital assets of the region, appraising how activities are creating pressures on these flows and whether the controls for these pressures protect them. Our risk register highlights how governance currently favours the protection of direct (extractive) benefit flows from natural capital assets of the region, which are primarily targeted for financial benefit. Without a systems-based framework that can account for the cumulative pressures on natural capital assets their status, associated ecosystem services and benefits are at risk. Such an approach is essential to capture and protect the foundational and often diffuse connections between marine natural capital and global society.

Filling the data gaps: Transferring models from data-rich to data-poor deep-sea areas to support spatial management - Amelia E.H. Bridges; David K.A. Barnes; James B. Bell; Rebecca E. Ross; Lizette Voges; Kerry L. Howell (Journal of Environmental Management, 2023)

A complex interplay among agricultural land uses, urbanization, and landscape attributes shapes the concentration-discharge relationships in Ontario, Canada - M. Georgina Kaltenecker; Carl P.J. Mitchell; E. Todd Howell; George Arhonditsis (Journal of Hydrology, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

The potential to increase grassland soil C stocks by extending reseeding intervals is dependent on soil texture and depth - Dafydd M.O. Elias; Kelly E. Mason; Katherine Howell; Nadine Mitschunas; Lucy Hulmes; Sarah Hulmes; Inma Lebron; Richard F. Pywell; Niall P. McNamara (Journal of Environmental Management, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Heavy metal ecotoxicology of vervet monkeys (Chlorocebus pygerythrus) across field sites in South Africa - James E. Loudon; Alycia E. Lewis; Trudy R. Turner; Michaela E. Howells; Alysha Lieurance; Jack E. Pender (Primates, 2022)

How thermal challenges change gene regulation in the songbird brain and gonad: Implications for sexual selection in our changing world - Sara E. Lipshutz; Clara R. Howell; Aaron M. Buechlein; Douglas B. Rusch; Kimberly A. Rosvall; Elizabeth P. Derryberry (Molecular Ecology, 2022)
In a rapidly warming world, exposure to high temperatures may impact fitness, but the gene regulatory mechanisms that link sublethal heat to sexually selected traits are not well understood, particularly in endothermic animals. Our experiment used zebra finches ( Taeniopygia guttata ), songbirds that experience extreme temperature fluctuations in their native Australia. We exposed captive males to an acute thermal challenge (43°C) compared with thermoneutral (35°C) and lower (27°C) temperatures. We found significantly more heat dissipation behaviours at 43°C, a temperature previously shown to reduce song production and fertility, and more heat retention behaviours at 27°C. Next, we characterized transcriptomic responses in tissues important for mating effort—the posterior telencephalon, for its role in song production, and the testis, for its role in fertility and hormone production. Differential expression of hundreds of genes in the testes, but few in the brain, suggests the brain is less responsive to extreme temperatures. Nevertheless, gene network analyses revealed that expression related to dopaminergic signalling in the brain covaried with heat dissipation behaviours, providing a mechanism by which temporary thermal challenges may alter motivational circuits for song production. In both brain and testis, we observed correlations between thermally sensitive gene networks and individual differences in thermoregulatory behaviour. Although we cannot directly relate these gene regulatory changes to mating success, our results suggest that individual variation in response to thermal challenges could impact sexually selected traits in a warming world.

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

Highly specific and rapid molecular detection of Candida glabrata in clinical samples - Oscar Hernández-Carreón; Cesia Hernández-Howell; Grecia Hernández-Hernández; M. Selene Herrera-Basurto; Blanca E. González-Gómez; Guadalupe Gutiérrez-Escobedo; Norma I. García-Calderón; Daniel Barrón-Pastor; Alejandro De Las Peñas; Irene Castaño (Brazilian Journal of Microbiology, 2021)

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

A Review of Applications Evaluating Fisheries Management Scenarios through Marine Ecosystem Models - H. A. Perryman; C. Hansen; D. Howell; E. Olsen (Reviews in Fisheries Science & Aquaculture, 2021)

Physiological diversity among sympatric, conspecific endosymbionts of coral (Cladocopium C1acro) from the Great Barrier Reef - V. H. Beltrán; E. Puill-Stephan; E. Howells; A. Flores-Moya; M. Doblin; E. Núñez-Lara; V. Escamilla; T. López; M. J. H. van Oppen (Coral Reefs, 2021)

Proteomic profiling of murine biliary-derived hepatic organoids and their capacity for drug disposition, bioactivation and detoxification - Lawrence Howell; Rosalind E. Jenkins; Stephen Lynch; Carrie Duckworth; B. Kevin Park; Christopher Goldring (Archives of Toxicology, 2021)
Hepatic organoids are a recent innovation in in vitro modeling. Initial studies suggest that organoids better recapitulate the liver phenotype in vitro compared to pre-existing proliferative cell models. However, their potential for drug metabolism and detoxification remains poorly characterized, and their global proteome has yet to be compared to their tissue of origin. This analysis is urgently needed to determine what gain-of-function this new model may represent for modeling the physiological and toxicological response of the liver to xenobiotics. Global proteomic profiling of undifferentiated and differentiated hepatic murine organoids and donor-matched livers was, therefore, performed to assess both their similarity to liver tissue, and the expression of drug-metabolizing enzymes and transporters. This analysis quantified 4405 proteins across all sample types. Data are available via ProteomeXchange (PXD017986). Differentiation of organoids significantly increased the expression of multiple cytochrome P450, phase II enzymes, liver biomarkers and hepatic transporters. While the final phenotype of differentiated organoids is distinct from liver tissue, the organoids contain multiple drug metabolizing and transporter proteins necessary for liver function and drug metabolism, such as cytochrome P450 3A, glutathione- S -transferase alpha and multidrug resistance protein 1A. Indeed, the differentiated organoids were shown to exhibit increased sensitivity to midazolam (10–1000 µM) and irinotecan (1–100 µM), when compared to the undifferentiated organoids. The predicted reduced activity of HNF4A and a resulting dysregulation of RNA polymerase II may explain the partial differentiation of the organoids. Although further experimentation, optimization and characterization is needed relative to pre-existing models to fully contextualize their use as an in vitro model of drug-induced liver injury, hepatic organoids represent an attractive novel model of the response of the liver to xenobiotics. The current study also highlights the utility of global proteomic analyses for rapid and accurate evaluation of organoid-based test systems.

Accommodating the role of site memory in dynamic species distribution models - Graziella V. DiRenzo; David A. W. Miller; Blake R. Hossack; Brent H. Sigafus; Paige E. Howell; Erin Muths; Evan H. C. Grant (Ecology, 2021)
First‐order dynamic occupancy models (FODOMs) are a class of state‐space model in which the true state (occurrence) is observed imperfectly. An important assumption of FODOMs is that site dynamics only depend on the current state and that variations in dynamic processes are adequately captured with covariates or random effects. However, it is often difficult to understand and/or measure the covariates that generate ecological data, which are typically spatiotemporally correlated. Consequently, the non‐independent error structure of correlated data causes underestimation of parameter uncertainty and poor ecological inference. Here, we extend the FODOM framework with a second‐order Markov process to accommodate site memory when covariates are not available. Our modeling framework can be used to make reliable inference about site occupancy, colonization, extinction, turnover, and detection probabilities. We present a series of simulations to illustrate the data requirements and model performance. We then applied our modeling framework to 13 yr of data from an amphibian community in southern Arizona, USA. In this analysis, we found residual temporal autocorrelation of population processes for most species, even after accounting for long‐term drought dynamics. Our approach represents a valuable advance in obtaining inference on population dynamics, especially as they relate to metapopulations.

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Transcriptomic analysis of hidradenitis suppurativa skin suggests roles for multiple inflammatory pathways in disease pathogenesis - Beth E. Rumberger; Erika L. Boarder; Sherry L. Owens; Michael D. Howell (Inflammation Research, 2020)

Comparing Deep-Sea Larval Dispersal Models: A Cautionary Tale for Ecology and Conservation - Rebecca E. Ross; W. Alex M. Nimmo-Smith; Ricardo Torres; Kerry L. Howell (Frontiers in Marine Science, 2020)

Annual outbreaks of coral disease coincide with extreme seasonal warming - E. J. Howells; G. O. Vaughan; T. M. Work; J. A. Burt; D. Abrego (Coral Reefs, 2020)

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Combining Distribution and Dispersal Models to Identify a Particularly Vulnerable Marine Ecosystem - Rebecca E. Ross; Edward J. G. Wort; Kerry L. Howell (Frontiers in Marine Science, 2019)

Variable responses of karst springs to recharge in the Middle Atlas region of Morocco - Brett A. Howell; Alan E. Fryar; Lahcen Benaabidate; Lhoussaine Bouchaou; Mohamed Farhaoui (Hydrogeology Journal, 2019)

Grain yield, evapotranspiration, and water-use efficiency of maize hybrids differing in drought tolerance - Baozhen Hao; Qingwu Xue; Thomas H. Marek; Kirk E. Jessup; Jacob D. Becker; Xiaobo Hou; Wenwei Xu; Edsel D. Bynum; Brent W. Bean; Paul D. Colaizzi; Terry A. Howell (Irrigation Science, 2019)

Human Ischaemic Cascade Studies Using SH-SY5Y Cells: a Systematic Review and Meta-Analysis - Ye Liu; Emma D. Eaton; Taryn E. Wills; Sarah K. McCann; Ana Antonic; David W. Howells (Translational Stroke Research, 2018)

Increasing connectivity between metapopulation ecology and landscape ecology - Paige E. Howell; Erin Muths; Blake R. Hossack; Brent H. Sigafus; Richard B. Chandler (Ecology, 2018)
Metapopulation ecology and landscape ecology aim to understand how spatial structure influences ecological processes, yet these disciplines address the problem using fundamentally different modeling approaches. Metapopulation models describe how the spatial distribution of patches affects colonization and extinction, but often do not account for the heterogeneity in the landscape between patches. Models in landscape ecology use detailed descriptions of landscape structure, but often without considering colonization and extinction dynamics. We present a novel spatially explicit modeling framework for narrowing the divide between these disciplines to advance understanding of the effects of landscape structure on metapopulation dynamics. Unlike previous efforts, this framework allows for statistical inference on landscape resistance to colonization using empirical data. We demonstrate the approach using 11 yr of data on a threatened amphibian in a desert ecosystem. Occupancy data for Lithobates chiricahuensis (Chiricahua leopard frog) were collected on the Buenos Aires National Wildlife Refuge ( BANWR ), Arizona, USA from 2007 to 2017 following a reintroduction in 2003. Results indicated that colonization dynamics were influenced by both patch characteristics and landscape structure. Landscape resistance increased with increasing elevation and distance to the nearest streambed. Colonization rate was also influenced by patch quality, with semi‐permanent and permanent ponds contributing substantially more to the colonization of neighboring ponds relative to intermittent ponds. Ponds that only hold water intermittently also had the highest extinction rate. Our modeling framework can be widely applied to understand metapopulation dynamics in complex landscapes, particularly in systems in which the environment between habitat patches influences the colonization process.

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Variation in particulate C : N : P stoichiometry across the Lake Erie watershed from tributaries to its outflow - Clay Prater; Paul C. Frost; E. Todd Howell; Susan B. Watson; Arthur Zastepa; Sarah S. E. King; Richard J. Vogt; Marguerite A. Xenopoulos (Limnology and Oceanography, 2017)
Human activities can cause large alterations in biogeochemical cycles of key nutrients such as carbon (C), nitrogen (N), and phosphorus (P). However, relatively little is known about how these changes alter the proportional fluxes of these elements across ecosystem boundaries from rivers to lakes. Here, we examined environmental factors influencing spatial and temporal variation in particulate C : N : P ratios across the Lake Erie watershed from its tributaries to its outflow. Throughout the study, particulate nutrient ratios ranged widely (C : N 2.0–25.8, C : P 32–530, N : P 3.7–122.9), but mean values were generally lower than previous estimates from different aquatic environments. Particulate C : N ratios varied the least across all environments, but C : P and N : P ratios increased between tributaries and coastal areas and throughout the growing season in coastal environments. These ratios also differed temporally in offshore waters as particulate C : P and N : P were higher in the spring and summer and lower in the fall and winter. Particulate C : P ratios also increased between the western/central and eastern basins indicating differential nutrient processing across the lake. These stoichiometric changes were associated with unique environmental factors among ecosystems as tributary stoichiometry was related to terrestrial land use and land cover, coastal ratios were a product of mixing between riverine and offshore waters, and offshore patterns were influenced by differences in temperature and particulate nutrient loading among basins. Overall, by studying changes in particulate C : N : P ratios across the Lake Erie watershed, our study demonstrates the power of using mass balance principles to study nutrient transformations along the aquatic continuum.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Population genetics of reef coral endosymbionts ( Symbiodinium , Dinophyceae) - D. J. Thornhill; E. J. Howells; D. C. Wham; T. D. Steury; S. R. Santos (Molecular Ecology, 2017)
Symbiodinium is a diverse genus of unicellular dinoflagellate symbionts associating with various marine protists and invertebrates. Although the broadscale diversity and phylogenetics of the Symbiodinium complex is well established, there have been surprisingly few data on fine‐scale population structure and biogeography of these dinoflagellates. Yet population‐level processes contribute strongly to the biology of Symbiodinium , including how anthropogenic‐driven global climate change impacts these symbionts and their host associations. Here, we present a synthesis of population‐level characteristics for Symbiodinium , with an emphasis on how phylogenetic affinities, dynamics within and among host individuals, and a propensity towards clonality shape patterns on and across reefs. Major inferences include the following: (i) Symbiodinium populations within individual hosts are comprised mainly of cells belonging to a single or few genetic clones. (ii) Symbiont populations exhibit a mixed mode of reproduction, wherein at least one sexual recombination event occurs in the genealogy between most genotypes, but clonal propagation predominates overall. (iii) Mutualistic Symbiodinium do not perpetually persist outside their hosts, instead undergoing turnover and replacement via the continuous shedding of viable clonal cells from host individuals. (iv) Symbiont populations living in the same host, but on different reefs, are often genetically subdivided, suggesting low connectivity, adaptation to local conditions, or prolific asexual reproduction and low effective population sizes leading to disproportionate success within and among hosts. Overall, this synthesis forms a basis for future investigations of coral symbiosis ecology and evolution as well as delimitation of species boundaries in Symbiodinium and other eukaryotic microorganisms.

Risk algorithms that include pathology adjustment for HER2 amplification need to make further downward adjustments in likelihood scores - D. G. Evans; E. R. Woodward; S. J. Howell; S. Verhoef; A. Howell; F. Lalloo (Familial Cancer, 2017)

Raman spectroscopic analysis of the effect of the lichenicolous fungus Xanthoriicola physciae on its lichen host - Howell G.M. Edwards; Mark R.D. Seaward; Tom F. Preece; Susana E. Jorge-Villar; David L. Hawksworth (Symbiosis, 2017)

Microsatellite allele sizes alone are insufficient to delineate species boundaries in Symbiodinium - E. J. Howells; B. L. Willis; L. K. Bay; M. J. H. van Oppen (Molecular Ecology, 2016)
Symbiodinium are a diverse group of unicellular dinoflagellates that are important nutritional symbionts of reef‐building corals. Symbiodinium putative species (‘types’) are commonly identified with genetic markers, mostly nuclear and chloroplast encoded ribosomal DNA regions. Population genetic analyses using microsatellite loci have provided insights into Symbiodinium biogeography, connectivity and phenotypic plasticity, but are complicated by: (i) a lack of consensus criteria used to delineate inter‐ vs. intragenomic variation within species; and (ii) the high density of Symbiodinium in host tissues, which results in single samples comprising thousands of individuals. To address this problem, Wham & LaJeunesse (2016) present a method for identifying cryptic Symbiodinium species from microsatellite data based on correlations between allele size distributions and nongeographic genetic structure. Multilocus genotypes that potentially do not recombine in sympatry are interpreted as secondary ‘species’ to be discarded from downstream population genetic analyses. However, Symbiodinium species delineations should ideally incorporate multiple physiological, ecological and molecular criteria. This is because recombination tests may be a poor indicator of species boundaries in Symbiodinium due to their predominantly asexual mode of reproduction. Furthermore, discontinuous microsatellite allele sizes in sympatry may be explained by secondary contact between previously isolated populations and by mutations that occur in a nonstepwise manner. Limitations of using microsatellites alone to delineate species are highlighted in earlier studies that demonstrate occasional bimodal distributions of allele sizes within Symbiodinium species and considerable allele size sharing among Symbiodinium species. We outline these issues and discuss the validity of reinterpretations of our previously published microsatellite data from Symbiodinium populations on the Great Barrier Reef (Howells et al . 2013).

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Habitat fragmentation in coastal southern C alifornia disrupts genetic connectivity in the cactus wren ( C ampylorhynchus brunneicapillus ) - Kelly R. Barr; Barbara E. Kus; Kristine L. Preston; Scarlett Howell; Emily Perkins; Amy G. Vandergast (Molecular Ecology, 2015)
Achieving long‐term persistence of species in urbanized landscapes requires characterizing population genetic structure to understand and manage the effects of anthropogenic disturbance on connectivity. Urbanization over the past century in coastal southern C alifornia has caused both precipitous loss of coastal sage scrub habitat and declines in populations of the cactus wren ( C ampylorhynchus brunneicapillus ). Using 22 microsatellite loci, we found that remnant cactus wren aggregations in coastal southern C alifornia comprised 20 populations based on strict exact tests for population differentiation, and 12 genetic clusters with hierarchical B ayesian clustering analyses. Genetic structure patterns largely mirrored underlying habitat availability, with cluster and population boundaries coinciding with fragmentation caused primarily by urbanization. Using a habitat model we developed, we detected stronger associations between habitat‐based distances and genetic distances than E uclidean geographic distance. Within populations, we detected a positive association between available local habitat and allelic richness and a negative association with relatedness. Isolation‐by‐distance patterns varied over the study area, which we attribute to temporal differences in anthropogenic landscape development. We also found that genetic bottleneck signals were associated with wildfire frequency. These results indicate that habitat fragmentation and alterations have reduced genetic connectivity and diversity of cactus wren populations in coastal southern C alifornia. Management efforts focused on improving connectivity among remaining populations may help to ensure population persistence.

Estimating dispersal distance in the deep sea: challenges and applications to marine reserves - Ana Hilário; Anna Metaxas; Sylvie M. Gaudron; Kerry L. Howell; Annie Mercier; Nélia C. Mestre; Rebecca E. Ross; Andreas M. Thurnherr; Craig Young (Frontiers in Marine Science, 2015)

Functional connectivity in frontal-striatal brain networks and cocaine self-administration in female rhesus monkeys - K. S. Murnane; K. S. Gopinath; E. Maltbie; J. B. Daunais; Q. K. Telesford; L. L. Howell (Psychopharmacology, 2015)

Changing sea ice conditions and marine transportation activity in Canadian Arctic waters between 1990 and 2012 - Larissa Pizzolato; Stephen E. L. Howell; Chris Derksen; Jackie Dawson; Luke Copland (Climatic Change, 2014)

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

The Development of the Washington State Emergency Department Opioid Prescribing Guidelines - Darin E. Neven; Jennifer C. Sabel; Donelle N. Howell; Russell J. Carlisle (Journal of Medical Toxicology, 2012)

In vitro to in vivo extrapolation and species response comparisons for drug-induced liver injury (DILI) using DILIsym™: a mechanistic, mathematical model of DILI - Brett A. Howell; Yuching Yang; Rukmini Kumar; Jeffrey L. Woodhead; Alison H. Harrill; Harvey J. Clewell; Melvin E. Andersen; Scott Q. Siler; Paul B. Watkins (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Solvent Removal and Spore Inactivation Directly in Dispensing Vials with Supercritical Carbon Dioxide and Sterilant - Jahna Howell; Fengui Niu; Shannon E. McCabe; Wei Zhou; Charles J. Decedue (AAPS PharmSciTech, 2012)

A deep chlorophyll maximum nourishes benthic filter feeders in the coastal zone of a large clear lake - Sairah Y. Malkin; Greg M. Silsbe; Ralph E. H. Smith; E. Todd Howell (Limnology and Oceanography, 2012)
Water column profiles demonstrated that a deep chlorophyll maximum (DCM) in the littoral zone of Lake Ontario intersected the benthos during the development of stratification. We hypothesized that elevated food supply near the lake bottom may be nourishing littoral‐zone benthic suspension feeders during this time. Chlorophyll fluorescence was monitored at three heights above the lake bottom, together with near‐bottom water velocity using down‐facing acoustic Doppler current profilers (ADCPs), at three coastal stations along a cross‐shore transect. Concurrently, growth rates of quagga mussels ( Dreissena bugensis ) caged at the lake bottom were compared with mussels suspended 2 m above the bottom. Over a 3‐month period beginning April, caged lake‐bottom mussels grew rapidly (mean biomass‐specific growth rate = 1.08 yr −1 ), while over a 3‐month period beginning July, bottom mussels experienced a decrease in biomass (−0.74 yr −1 ). Suspended mussels always grew significantly faster than bottom mussels (2.3 and 2.2 yr −1 in Apr and Jul experiments, respectively), affirming previously predicted growth inhibition on the lake bottom due to seston depletion. The different growth rate between seasons of the caged‐bottom mussels was most likely attributable to differences in near‐bottom chlorophyll concentrations. There was significantly higher chlorophyll a concentration near the lake bottom during the April experiment (average of two stations closest to shore = 2.7 µg L −1 ) relative to the July experiment (0.21 µg L −1 at the same stations). We suggest that littoral‐zone quagga mussels are nourished during the onset of stratification via development of a DCM.

How can we improve information delivery to support conservation and restoration decisions? - Nathaniel E. Seavy; Christine A. Howell (Biodiversity and Conservation, 2010)

Panel of synaptic protein ELISAs for evaluating neurological phenotype - Paul E. Gottschall; Joanne M. Ajmo; Autumn K. Eakin; Matthew D. Howell; Hina Mehta; Lauren A. Bailey (Experimental Brain Research, 2010)

Role of dopamine transporters in the behavioral effects of 3,4-methylenedioxymethamphetamine (MDMA) in nonhuman primates - William E. Fantegrossi; Rayna M. Bauzo; Daniel M. Manvich; Jose C. Morales; John R. Votaw; Mark M. Goodman; Leonard L. Howell (Psychopharmacology, 2009)

High genetic differentiation and cross-shelf patterns of genetic diversity among Great Barrier Reef populations of Symbiodinium - E. J. Howells; M. J. H. van Oppen; B. L. Willis (Coral Reefs, 2009)

Does sequence polymorphism of FLC paralogues underlie flowering time QTL in Brassica oleracea? - H. Razi; E. C. Howell; H. J. Newbury; M. J. Kearsey (Theoretical and Applied Genetics, 2008)

Regional hydrostratigraphy and groundwater flow modeling in the arsenic-affected areas of the western Bengal basin, West Bengal, India - Abhijit Mukherjee; Alan E. Fryar; Paul D. Howell (Hydrogeology Journal, 2007)

HMG-CoA reductase is regulated by salinity at the level of transcription in Haloferax volcanii - Kelly A. Bidle; Thomas E. Hanson; Koko Howell; Jennifer Nannen (Extremophiles, 2007)

Indole-3-carbinol-induced death in cancer cells involves EGFR downregulation and is exacerbated in a 3D environment - E. P. Moiseeva; L. H. Fox; L. M. Howells; L. A. F. Temple; M. M. Manson (Apoptosis, 2006)

Factors affecting the post‐release survival of cultured juvenile Pseudopleuronectes americanus - E. A. Fairchild; W. H. Howell (Journal of Fish Biology, 2004)
Laboratory experiments were performed with cultured and wild juvenile winter flounder Pseudopleuronectes americanus to evaluate differences in behaviour and adaptation affecting post‐release vulnerability to predation. Studies revealed that the cryptic abilities of cultured winter flounder increased over time. Sediment‐naïve, cultured fish required a minimum of 2 days to improve their burying skills and at least 90 days for colour adaptation to match the sediment. Cultured winter flounder selected sediments consisting of small grains and colours matching their own pigment. Cultured winter flounder, regardless of their colour, were significantly more vulnerable to predation by birds. Additionally, cultured fish reacted differently than wild winter flounder when exposed to cues from a potential predator.

Aquatic Snails from Mining Sites Have Evolved to Detect and Avoid Heavy Metals - H. Lefcort; D. P. Abbott; D. A. Cleary; E. Howell; N. C. Keller; M. M. Smith (Archives of Environmental Contamination and Toxicology, 2004)

Effects of drought on contrasting insect and plant species in the UK in the mid‐1990s - M. D. Morecroft; C. E. Bealey; O. Howells; S. Rennie; I. P. Woiwod (Global Ecology and Biogeography, 2002)
Aim We examined the effects of drought in the summer of 1995 and the subsequent year on contrasting species of plants, moths, butterflies and ground beetles. We tested whether population increases were associated with: (a) species of warm environments (b) species of dry environments (c) species with rapid reproduction (d) species with high rates of dispersal. Location The study was conducted at Environmental Change Network (ECN) sites throughout Great Britain and Northern Ireland. Methods Climate monitoring, recording of plant species in permanent plots, transect walking for butterflies, light trapping for moths and pitfall trapping for carabid beetles were used. Results There was an overall increase in the number of species recorded in permanent vegetation plots between 1994 and 1996, principally among the annual and biennial vascular plants, probably as a result of gap colonization in grasslands. Most butterfly and moth species increased between 1994 and 1995. Among the butterflies, a southern distribution and high mobility were associated with species tending to increase throughout the period 1994–96, whereas declining species tended to have a northern distribution. A similar number of carabid beetle species increased as decreased in the period 1994–96; decreasing species tended to be associated with lower temperatures and wetter soils. Conclusions Current climate change scenarios indicate that the incidence of droughts in the United Kingdom will increase. A series of dry, hot summers could lead to a rapid change in the population of some species although others, including many plants, may be more resilient. This may lead to complex changes in ecosystems and needs to be considered in planning conservation strategies.

Physical and transcriptional mapping of the X-linked cleft palate and ankyloglossia (CPX) critical region - Claire Braybrook; Georgina Warry; Gareth Howell; Vanessa Mandryko; Alfred Arnason; Arni Bjornsson; Mark T. Ross; Gudrun E. Moore; Philip Stanier (Human Genetics, 2001)

An integrated AFLP and RFLP Brassica oleracea linkage map from two morphologically distinct doubled-haploid mapping populations - R. L. Sebastian; E. C. Howell; G. J. King; D. F. Marshall; M. J. Kearsey (Theoretical and Applied Genetics, 2000)

Analysis of sheep T-cell receptor β-chain heterogeneity - Wayne A. Halsey; Brent E. Palmer; James C. DeMartini; M. D. Howell (Immunogenetics, 1999)

Telemetry system for monitoring anterior cruciate ligament graft forcesin vivo - E. L. McKee; D. P. Lindsey; M. L. Hull; S. M. Howell (Medical & Biological Engineering & Computing, 1998)

The hepatotoxic potential of combined toluene-chronic ethanol exposure - Stanley R. Howell; John E. Christian; Gary E. Isom (Archives of Toxicology, 1986)